AN ANALYSIS OF SHARIA ECONOMIC LAW ON THE VALUATION OF COASTAL ECOSYSTEMS AS ECONOMIC ASSETS IN THE CARBON MARKET - Shofa Robbani; Eka_Anggita Maharani; Ana Maria Ulfa; Kiki Mei Ayu; M. Shofil Fuad (Universitas Muhammadiyah Surabaya, 2026)
Carbon trading has become a market-based mechanism to reduce greenhouse gas emissions while promoting environmental sustainability. From an Islamic perspective, this mechanism can be aligned with sharia principles such as justice, barakah, and environmental stewardship. This study aims to analyze the valuation of coastal ecosystems as economic assets within the carbon market from the perspective of Sharia Economic Law. The research employs a descriptive qualitative method to examine the potential and challenges of integrating Sharia principles into carbon trading practices in Indonesia. The results demonstrate that coastal ecosystems, including mangroves, seagrass beds, and coastal wetlands, possess a significant carbon absorption capacity and substantial economic value. Their utilization in carbon markets is permissible in Islam, provided that transactions are conducted transparently and are free from riba, gharar, and maysir. Additionally, fairness in the distribution of benefits to coastal communities must be ensured. Carbon market governance should prioritize public welfare, environmental protection, and social justice. Therefore, sharia-based regulatory frameworks are necessary to ensure that carbon trading not only generates economic benefits but also supports sustainability and community well-being.